Electrospinning Synthesis of Carbon-Supported Pt3Mn Intermetallic Nanocrystals and Electrocatalytic Performance towards Oxygen Reduction Reaction - Lechao Peng; Lan Zhou; Wenjun Kang; Rui Li; Konggang Qu; Lei Wang; Haibo Li (Nanomaterials, 2020)
To realize the large-scale application of fuel cells, it is still a great challenge to improve the performance and reduce the cost of cathode catalysts towards oxygen reduction reaction (ORR). In this work, carbon-supported ordered Pt3Mn intermetallic catalysts were prepared by thermal annealing electrospun polyacrylonitrile nanofibers containing Platinum(II) acetylacetonate/ Manganese(III) acetylacetonate. Compared with its counterparts, the ordered Pt3Mn intermetallic obtained at 950 °C exhibits a more positive half-potential and higher kinetic current density during the ORR process. Benefiting from their defined stoichiometry and crystal structure, the Mn atoms in Pt3Mn intermetallic can modulate well the geometric and electronic structure of surface Pt atoms, endowing Pt3Mn catalyst with an enhanced ORR catalytic activity. Moreover, it also has a better catalytic stability and methanol tolerance than commercial Pt/C catalyst. Our study provides a new strategy to fabricate a highly active and durable Pt3Mn intermetallic electrocatalyst towards ORR.